2015
DOI: 10.1515/amm-2015-0082
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Nanocrystalline Structure In X37CrMoV5-l Steel

Abstract: The aim of the study was to investigate the thermal stability of the nanostructure produced in X37CrMoV5-1 tool steel by austempering heat treatment consisted of austenitization and isothermal quenching at the range of the bainitic transformation. The nanostructure was composed of bainitic ferrite plates of nanometric thickness separated by thin layers of retained austenite. It was revealed, that the annealing at the temperature higher than temperature of austempering led to formation of cementite precipitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Steel is similar in chemical composition when compared to the previous one, except that the main chromium alloying element is less than half that of the previous steel. This tool steel is designed for very stressed tools such as dies, hot cutting tools, and knives [21]. Lower carbon content in steel reduces wear resistance.…”
Section: Methodsmentioning
confidence: 99%
“…Steel is similar in chemical composition when compared to the previous one, except that the main chromium alloying element is less than half that of the previous steel. This tool steel is designed for very stressed tools such as dies, hot cutting tools, and knives [21]. Lower carbon content in steel reduces wear resistance.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the austempering heat treatment that allowed obtaining a nanobainitic microstructure, the microstructure itself and mechanical properties of X37CrMoV5-1 nanobainitic steel are described elsewhere. [5,24,25] Two variants of low-temperature glow discharge carbon coating production were carried out. The first was a single low-temperature carbon coating production in glow discharge conditions at 400°C for 20 minutes in a mixture of CH 4 and N 2 (GDCC).…”
Section: Materials and Methodologymentioning
confidence: 99%
“…[1][2][3][4] However, recent studies have shown that in some commercial steel grades, e.g., X37CrMoV5-1 hot working tool steel, a nanobainitic microstructure, which improves the mechanical properties of this steel, can also be produced. [5] Unfortunately, the reduced carbon content in this steel affects the stability of residual austenite. Unstable austenite can undergo martensitic transformation during final cooling after heat treatment or under stress, which increases the hardness of the material and reduces its resilience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] The structure consists mostly of alternating thin plates of bainitic ferrite, a b , and retained austenite, c r , with a small fraction of retained austenite blocks forming the residue of the sample. The austenite films and bainite plates are typically below 50 nm in width, providing a potent strengthening mechanism without compromising toughness.…”
Section: Introductionmentioning
confidence: 99%